Modern Methods of Diagnosis and Treatment of Crohn’s Disease (Global Journal of Medical Research, 2025)
A study was conducted involving 94 patients diagnosed with Crohn s Disease CD The complications of CD included colonic hemorrhage strictures of the small and large intestines colonic pseudopolyposis interintestinal and interorgan fistulas and rectal fistulas For complicated cases of CD after a short-term course of conservative treatment and appropriate preparation considering co-existing diseases 61 64 8 patients underwent radical surgical interventions such as colectomy or resection of the affected bowel segment The choice of surgical method and volume depended on the extent of bowel involvement and the type of CD complications